Preparation of Natural Zeolite for Air Dehumidification in Food Drying - Mohamad Djaeni; Laeli Laeli Kurniasari; Setia Budi Sasongko (Chemical Engineering Diponegoro University, 2015)
Drying with air dehumidification with solid adsorbent improves the quality of food product as well as energy efficiency. The natural zeolite is one of adsorbent having potential to adsorb the water. Normally, the material was activated to open the pore, remove the organic impurities, and increase Si/Al rate. Hence, it can enhance the adsorbing capacity. This research studied the activation of natural zeolite mined from Klaten, Indonesia as air dehumidification for food drying. Two different methods were used involving activation by heat and NaOH introduction. As indicators, the porosity and water loaded were evaluated. Results showed both methods improved the adsorbing capacity significantly. With NaOH, the adsorbing capacity was higher. The simple test in onion and corn drying showed the presence of activated natural zeolite can speed up water evaporation positively. This performance was also comparable with Zeolite 3A